Early CCR6 expression on B cells modulates germinal centre kinetics and efficient antibody responses. Issue 1 (30th August 2016) - Reimer, Dorothea; Lee, Adrian YS; Bannan, Jennifer; Fromm, Phillip; Kara, Ervin E; Comerford, Iain; McColl, Shaun; Wiede, Florian; Mielenz, Dirk; Körner, Heinrich
Abstract : The CC‐chemokine receptor 6 (CCR6) can be detected on naive and activated B cells. Counterintuitively, its absence accelerates the appearance of germinal centres (GCs) and increases the production of low‐affinity antibodies. The detailed mechanism of CCR6 function during the humoral response has remained elusive, but previously we identified a distinct CCR6 high B‐cell population in vivo early after antigenic challenge. In this study, we defined this population specifically as early, activated pre‐GC B cells. In accordance, we show that CCR6 is upregulated rapidly within hours on the protein or mRNA level after activation in vitro . In addition, only activated B cells migrated specifically towards CCL20, the specific ligand for CCR6. Lack of CCR6 increased the dark zone/light zone ratio of GC and led to decreased antigen‐specific IgG1 and IgG2a antibody generation in a B‐cell intrinsic manner in mixed bone marrow chimeras. In contrast, antigen‐specific IgM responses were normal. Hence, CCR6 negatively regulates entry of activated, antigen‐specific pre‐GC B cells into the GC reaction.